Application of House of Risk (Hor) Models for Risk Mitigation of Procurement in The Balikpapan Samarinda Toll Road Project - Doddy Arief Wibowo; Ervina Ahyudanari (Institut Teknologi Sepuluh Nopember, 2020)
The Balikpapan Samarinda Toll Road Project built 99 km has a relatively short implementation time of 3 years. The accuracy of project completion is closely related to the procurement of materials during the implementation period. Risk analysis based on ISO 31000: 2009 where the risk of delay in procurement of materials is included in the extreme category with a high level of probability and severe impact. Risk analysis is carried out qualitatively, that is, determining risk priorities by determining the likelihood of events and their effects on project performance. Material procurement delays still occur due to various factors that have not been mitigated in the planned risk analysis. This resulted in project performance not on schedule. The purpose of this study is to provide a proactive framework for managing material procurement risks. The method used is the House of Risk (HOR) from the literature study. The HOR method is very commonly used in supply chain risk management. The HOR method focuses on preventive actions determining the main risk agents and the priority of preventive actions. The advantages of this method are in the framework that can cover the whole process of risk management. Phase 1 of HOR begins with the identification of risk events and phase 2 of risk treatment. This framework allows management to select priority risk agents to be mitigated and prioritize proactive actions to reduce the impact of risk events. The results of the study are 14 risk events and 15 risk agents that can occur in the material procurement process. From the Paretto Diagram, 4 risk agents were selected, namely schedule changes became faster, bill payments required a long period of time, problems in supplier selection, and material fabrication time. Based on the analysis of preventive action 3 actions proposed in this study are coordinating with the finance department to monitor supplier bills, coordinate with production for proper procurement schedules, and evaluate suppliers.